Male mate choice, male quality, and the potential for sexual selection on female traits under polygyny. (29th November 2016) - Fitzpatrick, Courtney L.; Servedio, Maria R.
Abstract : Observations of male mate choice are increasingly common, even in species with traditional sex roles. In addition, female traits that bear the hallmarks of secondary sexual characters are increasingly reported. These concurrent empirical trends have led to the repeated inference that, even under polygyny, male mate choice is a mechanism of sexual selection on female traits. It is often either assumed or argued that in these cases females are competing for males of superior "quality"; females might experience sexual selection under polygyny if they compete for mates that provide either direct or indirect benefits. However, the theoretical foundation of this testable hypothesis remains largely uninvestigated. We develop a population genetic model to probe the logic of this hypothesis and demonstrate that, contrary to common inferences, male mate choice, variation in male quality (in the form of a direct fecundity benefit to females), and female ornamentation can coexist in a population without any sexual selection on female ornamentation taking place at all. Furthermore, even in a "best case scenario" where high quality males with a preference for ornamented females are able to mate disproportionately more often with them, the evolution of female traits by sexual selection may be relatively weak. We discuss the implication of these findings for ongoing empirical and theoretical research on the evolution of sexual‐signaling in females.